“Deconstruction of Ethology” A Reading of Jacques Derrida in the Light of the Ethological Debate (Altre Modernità, 2021)
Derrida developed his most famous reflections on Animality in the Seminars: The Beast & The Sovereign (2001-2003). My hypothesis is that there we can find Derrida’s explicit interest for the ethological debate and its development. Indeed, I will show how deconstruction and ethological science are strictly connected for many reasons. If the historical scientific development of ethological sciences promoted the deconstruction of anthropomorphism (K. Lorenz, 1962), anthropocentrism (D. R. Griffin, 1979) and logocentrism (C. Safina, 2015; A. Neven, 2020), the theory of deconstruction uses these results with the aim to develop new conceptualities over the limits between Animals and Man. Thus, my aim will be to track the conceptual points of connection between Ethology and Deconstruction considering also the recent develops of cognitive and post-cognitive animal studies.
Keywords: Biodeconstruction; Jacques Derrida; Ethology; Autoimmunity; anthro-pocentrism; anthropomorphism; Carl Safina